Brainstem Reflexes in Systemic Lupus Erythematosus Patients Without Clinical Neurological Manifestations - SÜNTER, GÜLİN; ULUÇ, KAYIHAN; KAHRAMAN KOYTAK, PINAR; TANRIDAĞ, TÜLİN (AVES, 2017)
Introduction: We aimed to assess central and peripheral nervous system involvement in systemic lupus erythematosus (SLE) patients without any neurological signs and symptoms by performing electrophysiological investigations. Methods: Thirty-eight SLE patients and 35 healthy volunteers participated in this study. Peripheral nerve conduction and brainstem reflexes were evaluated by performing nerve conduction studies (NCSs) and blink reflex (BR) and masseter inhibitory reflex (MIR) recordings. Results: Eleven patients (29%) had an abnormality in at least 1 NCS parameter, and 1 (2.6%) patient was diagnosed with polyneuropathy. The number of patients with abnormal BR and MIR was 23 (60.5%) and 14 (37%), respectively. The contralateral R2 latency of BR and the silent period 1 (SP1) latency of MIR were significantly prolonged in the patients compared with the controls (p=0.015 and p<0.001, respectively). Conclusion: This study showed that irrespective of peripheral nervous system involvement, brainstem reflexes could be affected in SLE patients even without clinical neurological findings. Brainstem reflex abnormalities suggested that the functional integrity of the inhibitory or excitatory interneurons in the lateral caudal pons and lateral medulla is disturbed in SLE patients.
Keywords: Systemic lupus erythematosus; brainstem reflexes; electroneuromyography; peripheral nervous system; PERIPHERAL NEUROPATHY; DISEASE